Original Mechanochemical Synthesis of Non-Platinum Group Metals Oxygen Reduction Reaction Catalysts Assisted by Sacrificial Support Method. (10th October 2015) - Serov, Alexey; Artyushkova, Kateryna; Andersen, Nalin I.; Stariha, Sarah; Atanassov, Plamen
Graphical abstract: Abstract: Mechanochemical synthesis of non-platinum group metal catalysts for fuel cells is shifting the synthesis paradigm away from liquid chemistry to materials processing that is more benign and scalable for manufacturing. Mechanochemical synthesis is practiced in conjunction with the sacrificial support method for the preparation of Fe- Methylenediantipyrine (Fe-DAAPyr) cathode catalysts. This is a new catalyst from the transition Metal-Nitrogen-Carbon family, which is viewed as the most promising for practical applications and technology introduction. Detailed characterization using scanning electron microscopy, X-ray photoelectron spectroscopy and rotating ring disk electrode reveals correlations between activity and structural properties defining the differences in the mechanism of the oxygen reduction reaction (ORR) in acid and alkaline media. In an alkaline environment, an outer-sphere electron transfer is facilitated by the presence of hydroxyls rather than the contribution of active centers established from structure-to-property correlations found in acid. In acid, an increase in the numbers of defect sites, manifested by the presence of carbon oxides, leads to the increase in ORR activity.